2023
DOI: 10.1101/2023.07.22.550168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The spatial extent of anatomical connections within the thalamus varies across the cortical hierarchy in humans and macaques

Abstract: The thalamus is composed of functionally and structurally distinct nuclei. Previous studies have indicated that certain cortical areas may project across multiple thalamic nuclei, potentially allowing them to modulate distributed information flow. However, there is a lack of quantitative investigations into anatomical connectivity patterns within the thalamus. Consequently, it remains unknown if cortical areas exhibit differences in the spread of their thalamic connectivity patterns. To address this knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 142 publications
3
0
0
Order By: Relevance
“…Additionally, they found that matrix cell regions tend to couple to cortical areas with a lower intrinsic timescale (Müller et al, 2020). Thus, overall both gradients pointed to a differentiation between sensorimotor and transmodal networks, mirroring observations in recent work of a sensorimotor and association ‘motif’ of thalamic cortical patterning (Howell et al, 2023). Extending this work, we illustrated how these motifs may be embedded within the intrinsic organization of the thalamus along two main structurally defined gradients.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, they found that matrix cell regions tend to couple to cortical areas with a lower intrinsic timescale (Müller et al, 2020). Thus, overall both gradients pointed to a differentiation between sensorimotor and transmodal networks, mirroring observations in recent work of a sensorimotor and association ‘motif’ of thalamic cortical patterning (Howell et al, 2023). Extending this work, we illustrated how these motifs may be embedded within the intrinsic organization of the thalamus along two main structurally defined gradients.…”
Section: Discussionsupporting
confidence: 84%
“…This observation may arise due to the exclusion of the LGN from our thalamic mask (projects to primary visual cortex; Jones, 1985;Leh et al, 2008), and further may be driven by the projections of the Pulvinar encompassing higher-order areas and the visual system (Barron et al, 2015). The distinction of sensorimotor and association areas based on structural and functional connectivity aligned with previous work in humans and animals (Jones, 1998;Mukherjee et al, 2020;Harris et al, 2019;Howell et al, 2023) that illustrated how the thalamus may be a key node in the brain coordinating both sensorimotor and abstract cognitive functions (Shine et al, 2023;Wolff et al, 2021).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation